2017
DOI: 10.3847/1538-4357/aa74c1
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Characteristics of Zebra Patterns in Type IV Solar Radio Bursts

Abstract: The polarization characteristics of zebra patterns (ZPs) in type IV solar bursts were studied. We analyzed 21 ZP events observed by the Assembly of Metric-band Aperture Telescope and Real-time Analysis System between 2010 and 2015 and identified the following characteristics: a degree of circular polarization (DCP) in the range of 0%-70%, a temporal delay of 0-70 ms between the two circularly polarized components (i.e., the right-and left-handed components), and dominant ordinary-mode emission in about 81% of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…The induced plasma emissions at H and F bands are obtained through nonlinear wave-wave interaction, consistent with our earlier study (Ni et al 2020). The H emission dominates over the F emission in intensity by about 2 orders in magnitude, this indicates that the ZPs arise from the H emission, rather than the F emission as assumed in many studies (e.g., Zlotnik et al 2014;Chernov 2015;Kaneda et al 2017). The peak-valley contrast of intensity of the H emission is found to be ∼ 4, consistent with some observational reports.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…The induced plasma emissions at H and F bands are obtained through nonlinear wave-wave interaction, consistent with our earlier study (Ni et al 2020). The H emission dominates over the F emission in intensity by about 2 orders in magnitude, this indicates that the ZPs arise from the H emission, rather than the F emission as assumed in many studies (e.g., Zlotnik et al 2014;Chernov 2015;Kaneda et al 2017). The peak-valley contrast of intensity of the H emission is found to be ∼ 4, consistent with some observational reports.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…The reason for this remains an open question, but a common explanation is that scattering of the radio emission by other wave modes or by sharp density gradients tends to have a depolarizing effect (e.g. Wentzel, Zlobec, and Messerotti, 1986;Melrose, 1989Melrose, , 2006Kaneda et al, 2017). The polarization fraction of harmonic [2f p ] emission is more complicated because it depends on the angular distribution of the Langmuir waves.…”
Section: Introductionmentioning
confidence: 99%
“…While type IV radio bursts are known to be radiated from energetic electrons trapped in closed magnetic loops of the solar corona through the synchrotron emission process, fine spectral structures are embedded on it. Kaneda et al [2015;2017] found a zebra pattern (ZP) in a type IV solar radio burst and investigated the polarization characteristics. Analyzing highly resolved spectral and polarization data revealed the frequency dependence of the degree of circular polarization and the delay between two polarized components for the first time.…”
Section: Specification Of Amateras and On-line Databasementioning
confidence: 99%